"We have to join forces..." - Current status and future European policies as discussed at the One Health EJP conference "Collaborating to face future One Health challenges in Europe" - Ludovico P. Sepe; Pikka Jokelainen; Jennifer Cantlay; Roberto La Ragione; Annemarie Käsbohrer (CABI, 2024)
Abstract Ideally, discussions on the One Health policy should bring together actors from several sectors. This was the case at the conference organised by the One Health European Joint Programme (One Health EJP) "Collaborating to face future One Health challenges in Europe", which took place from the 19 to the 21 June 2023 in Brussels, Belgium. Here we report on the discussions and interactions that occurred among lead European One Health stakeholders from the animal health, public health, wider environmental (including ecosystem health), and social sciences sectors, coming from the public and private sectors, and non-governmental organisations. The participants included policy makers, risk assessors, risk managers, experts from the academia, as well as representatives of national, European, and international organisations. The conference served two purposes. First, it highlighted the achievements of the One Health EJP on prevention, detection, and response to health threats. Second, it served as a forum to discuss current and future European One Health policies, analysing interactions across sectors, and setting the scene for the One Health policy agenda of tomorrow. In this article, we highlight the main messages and viewpoints of a wide range of European stakeholders on One Health and its future needs. Discussions covered topics such as policies of the European Commission, operationalisation of these policies through EU agencies, the broadening of the One Health concept to increasingly integrate sectors other than public health and animal health, and the role of the private sector in One Health initiatives. These dialogues gave insights into future One Health policies, providing information that integrate the publicly available policy documents, and aiming at shaping the European One Health approach in preparation for upcoming challenges.